Confocal laser endomicroscopy reveals alterations in duodenal permeability in patients with acute pancreatitis. Issue 3 (March 2019) - Sun, Lingjia; Yue, Min; Dai, Yining; Yu, Chaohui; Chen, Chunxiao
Objective: Intestinal permeability increases during the course of acute pancreatitis (AP). We assessed duodenal permeability alterations in patients with AP by confocal laser endomicroscopy (CLE). Methods: Thirty patients with AP underwent CLE evaluation of the antral and duodenal mucosa. Images were graded based on the appearance of capillaries and the degree of fluorescein leakage. Results: Patients with AP had increased duodenal mucosal permeability that could be detected by CLE. The mucosal permeability progressively increased in the gastric antrum, duodenal bulb, and descending duodenum. The CLE parameters in the antrum and duodenal bulb were not significantly different between patients with mild and severe AP. The CLE grades in the descending duodenum were higher in patients with severe than mild AP. The C-reactive protein level in AP was positively correlated with the permeability in the duodenal bulb and descending duodenum, while the computed tomography severity index score was positively correlated with the mucosal permeability in the duodenal bulb and descending duodenum. Conclusion: CLE revealed increased duodenal permeability in patients with AP. Higher permeability in the descending duodenum was observed in severe than mild AP. Further large-scale studies are needed to confirm the relationship between altered duodenal permeability and the severity of AP.